The occurrence of Spinosauridae (Dinosauria: Theropoda) during the Cretaceous of Asia: Implications for biogeography and distribution - Samathi, Adun; Puntanon, Kridsanupong (Thai Geoscience Journal, 2025)
The theropod dinosaur clade Spinosauridae lived on almost all continents during the Cretaceous. It has been suggested that the group originated in Laurasia, likely in Europe. Asian spinosaurid fossils have been discovered in Southeast and East Asia, particularly from Barremian–Aptian deposits of the Early Cretaceous, with some additional evidence from Cenomanian-aged sediments in the Late Cretaceous. The presence of this theropod clade in Asia, including Thailand, Malaysia, Laos, China, and Japan, may have been influenced by the regression of the Uralian seaway, which temporarily connected Europe and Asia via an ephemeral landbridge. This change likely affected the dispersal of spinosaurids from Europe, facilitating their spread across Asia and shaping their evolution through geographic vicariance. This study reviews the Asian fossil record of Spinosauridae to examine their emergence, paleogeographic distribution, and dispersal patterns. The reports of Asian spinosaurids suggested that the distribution of this clade in Asia is complex and dubious due to the incompleteness of materials and uncertainty of the age of several fossil-bearing strata. The spinosaurid ancestors dispersed along the coastal shoreline from Europe by crossing ephemeral landbridge during pre-Barremian. Then, they spread out to Thailand, Malaysia, southern China, and Japan. The presence of Late Cretaceous spinosaurids in China suggests that Asian spinosaurids persisted until the extinction event of this clade, as happened in western Laurasia and Gondwana during the Cenomanian.